THE ROLE OF GRAMMAR IN TEACHING ENGLISH LANGUAGE - Nurmanov , Shavkat Mirolimovich (Educational Research in Universal Sciences, 2023)
This article is devoted to the brief clarification of how grammar can serve as a language teaching source by comparing them according to their functionality.